Annotated checklist of marine molluscs collected during the R. V. Victor Hensen Costa Rica Expedition 1993/1994 - Cruz Soto, Rafael (1995)
An annotated checklist of species of marine molluscs from Golfo Dulce, Bahfa Coronado and Golfo de Nicoya. Costa Rica, obtained aI 20-200 m during the Victor Hensen cruise, includes 157 species: 108 Gastropoda and 49 Pelecypoda. The checklist includes station and depth data for all species